Golgi Reassembly and Stacking Protein: biophysical properties and their functional implications - Fontana, Natália Aparecida (2021)
GRASPs (from Golgi ReAssembly and Stacking Proteins) are proteins involved in the organization and maintenance of the Golgi complex. While the extension of this role has been questioned in the past few years, many other functions have been assigned to them. In particular, we highlight the participation in tethering vesicles that need to move along the Golgi and processes of unconventional protein secretion. Structurally, GRASPs can be divided in an N-terminal domain called GRASP and a non-conserved, highly disordered C-terminal domain, termed SPR. Structural information, hitherto, has been scarce, which motivated the beginning of this project. To study GRASPs, we used the only GRASP (called Grh1) of a model organism: the yeast Saccharomyces cereviseae. We showed that Grh1 contains regions of intrinsic disorder also in its GRASP domain, being classified as a molten globule. Besides, Grh1 is capable of forming amyloid-like fibrils when in specific conditions in vitro, such as low pH and moderately elevated temperature. With the aim of investigating a possible relationship between fibril formation and the role played by Grh1 in unconventional protein secretion, part of the present thesis was done in vivo, and it was possible to demonstrate that the yeast GRASP fibrillates in starvation and heat-shock conditions. Here, we discuss the use of Fluorescence Lifetime Imaging Microscopy as a valid technique to help detect fibril formation in cell and also the possible implications of fibrillation for the formation of the Compartments for Unconventional Protein Secretion (CUPS). This work also contains initial experiments that point to a liquid-liquid phase separation of Grh1, an observation in consonance with the findings of intrinsic disorder and the recent proposition that the Golgi is actually an organelle phase separated from the cytosol. Finally, we present initial experiments of the characterization of Bug1, the golgin partner of Grh1. There are no structural data available on golgins in solution yet and their purification always presented an obstacle on obtaining them. We describe here a protocol capable of purifying Bug1 in high quantities, therefore paving the way for many other discoveries in the fields of protein secretion and liquid-liquid phase separation.